The Microbiome in Critical Illness - Nathan J. Klingensmith; Jennifer M. Leonard; Patricia Martinez-Quinones; Cherylee W.J. Chang; Ravinder Nagpal; Philip A. Efron; Marlies Ostermann; Gail A.M. Cresci; Robert C. Keskey; John C. Alverdy; Craig M. Coopersmith; Lewis J. Kaplan (Critical Care Medicine, 2026)
Objectives: To review how the human microbiome impacts management of the critically ill or injured patient. Data Sources: English-language manuscripts were sourced from PubMed and OVID from inception to August 2025. Study Selection: Manuscripts addressing the mammalian microbiome, microbiome characterization, microbiome derangement, microbiome restoration, critical care interventions, the ICU, and organ system outcomes related to the human microbiome. Gray literature was excluded. Data Extraction: Data that informed microbiome characterization, derangement, support, manipulation, as well as the impact of the microbiome on critical care medicine interventions or outcomes were abstracted. Data Synthesis: Humans demonstrate a variety of unique microbiomes spanning eyes, skin, oropharynx, lung, bladder, and gastrointestinal tract. The most identifiable active outside of the lifecycles of resident microbiota is the gastrointestinal microbiome. The gastrointestinal microbiome plays a critical role in health maintenance as well as the physiologic recovery—or failure—of the critically ill or injured. Microbial balance disruption is common in ICU patients due to index admission disease processes as well as rescue or management therapeutics. Understanding how disease-modulated and therapy-driven microbiome changes occur—as well as their impact—may reveal strategies to improve critical care outcomes. The gastrointestinal microbiome serves as a lens through which microbial actions and host-microbe-regulated functions may be understood. Conclusions: Based on the impact of the human microbiome on critical care-relevant interventions and outcomes, the ICU clinician will benefit from understanding: 1) microbiome evaluation fundamentals, 2) microbiome adaptive or maladaptive alteration by disease process as well as therapeutic agents, and 3) current and emerging interventions to mitigate pathobiome induction and restore homeostasis to improve outcomes.